2015
DOI: 10.1371/journal.pone.0121810
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effects of Cardiovascular Risk Factors on Endothelium-Dependent Dilation and Endothelin Activity in Middle-Aged Women and Men

Abstract: BackgroundHealthy middle-aged postmenopausal women have higher endothelium-dependent dilation and lower vasoconstrictor activity of endothelin-1 than men. Whether these sex-specific differences extend to patients with cardiovascular risk factors has not been investigated. The current study aimed to determine whether, in patients with cardiovascular risk factors, sex-specific differences exist in endothelium-dependent dilation and endothelin-1 activity.MethodsForearm blood flow responses were measured by strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Healthy women have been shown to have higher endothelium‐dependent dilation when compared to their male counterparts, and the presence of cardiovascular risk factors has been associated with sex‐specific effects on endothelium‐dependent dilation 8. The Women's Ischemic Syndrome Evaluation study also suggested that sex plays a role in development of atherosclerosis, reporting increased likelihood of diffuse plaque formation in women when compared to men who developed discrete coronary lesions 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy women have been shown to have higher endothelium‐dependent dilation when compared to their male counterparts, and the presence of cardiovascular risk factors has been associated with sex‐specific effects on endothelium‐dependent dilation 8. The Women's Ischemic Syndrome Evaluation study also suggested that sex plays a role in development of atherosclerosis, reporting increased likelihood of diffuse plaque formation in women when compared to men who developed discrete coronary lesions 9.…”
Section: Introductionmentioning
confidence: 99%
“…7 Healthy women have been shown to have higher endotheliumdependent dilation when compared to their male counterparts, and the presence of cardiovascular risk factors has been associated with sex-specific effects on endotheliumdependent dilation. 8 The Women's Ischemic Syndrome Evaluation study also suggested that sex plays a role in development of atherosclerosis, reporting increased likelihood of diffuse plaque formation in women when compared to men who developed discrete coronary lesions. 9 Moreover, men have been shown to have a greater atheroma burden with more eccentric atheroma and diffuse epicardial endothelial dysfunction than women, suggesting increased structural and functional epicardial abnormalities when compared to their female counterparts.…”
mentioning
confidence: 99%
“…Estrogens have a protective role in this regard in premenopausal women. However, after the decrease in estrogen levels, women are exposed to the same, or even higher, cardiovascular risks as males [ 18 , 19 ]. Because of this, we examined the echocardiography of the mice, especially the ejection fraction (EF) and fractional shortening (FS), which are the two most commonly used parameters for estimating cardiac function, in the two groups using a Vevo®1100 Imaging system.…”
Section: Resultsmentioning
confidence: 99%
“…Ovarian aging, which refers to the physiological process of active loss of ovarian function in females before they age, is considered as a gain-of-function mutation that can effectively avoid the physiological burden and life threatening of the maternal body brought by the elderly pregnancy 1 . However, ovarian aging is not just the loss of reproductive capability, the lack of gonadal hormones caused by it can trigger many diseases including cardiovascular disease, cancer, osteoporosis, obesity and menopausal syndrome [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%